Search for resonant and nonresonant Higgs boson pair production in the bb [bar] [tau] + [tau] - decay channel in pp collisions at √s=13 TeV with the ATLAS detector - Aaboud, Morad; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Jongmanns, Jan; Kolb, Mathis; Kugel, Andreas; Meyer zu Theenhausen, Hanno; S̜ahinsoy, Merve; Schöning, André; et al. (Physical review letters, 2018)
A search for resonant and nonresonant pair production of Higgs bosons in the b¯bτ+τ− final state is presented. The search uses 36.1 fb−1 of pp collision data with √s=13 TeV recorded by the ATLAS experiment at the LHC in 2015 and 2016. Decays of the τ-lepton pairs with at least one τ lepton decaying to final states with hadrons and a neutrino are considered. No significant excess above the expected background is observed in the data. The cross-section times branching ratio for nonresonant Higgs boson pair production is constrained to be less than 30.9 fb, 12.7 times the standard model expectation, at 95% confidence level. The data are also analyzed to probe resonant Higgs boson pair production, constraining a model with an extended Higgs sector based on two doublets and a Randall-Sundrum bulk graviton model. Upper limits are placed on the resonant Higgs boson pair production cross-section times branching ratio, excluding resonances X in the mass range 305 GeV<mX<402 GeV in the simplified hMSSM minimal supersymmetric model for tanβ=2 and excluding bulk Randall-Sundrum gravitons GKK in the mass range 325 GeV<mGKK<885 GeV for k/¯MPl=1.
M. Aaboud, A.E. Bolz, O. Brandt, M. Dunford, D.E. Ferreira de Lima, S. Franchino, J. Jongmanns, M. Kolb, A. Kugel, H. Meyer Zu Theenhausen, F. Napolitano, M. Sahinsoy, A. Schoening, H-C. Schultz-Coulon, D. Sosa, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, J. Wang, S.M. Weber, M. Wessels, X. Yue [und weitere] (ATLAS Collaboration)
Im Titel sind "+" und "-" hochgestellt
Im Titel wird "tau" als griechischer Buchstabe dargestellt
Gesehen am 16.07.2019